Dynamic adaptation in the serious games for the development of the learning of mathematics in children with learning problems - Jácome-Amores, Ligia (2019)
This article presents a study on the impact of a Serious Game (SG), developed to strengthen learning in children in the area of mathematics. The methodology used was based on three phases: in the first, an exploratory research was conducted through surveys and unstructured interviews with authorities and teachers from two educational centers in Tungurahua (Ecuador). In the second, the SG was developed, applying an adaptive algorithm in its architecture, so that it is always entertaining and challenging. Finally, in the third, a quasi-experimental study was carried out in which 50 children of school age participated, of which 50% suffer from mild intellectual disability. The quantitative results showed significant statistical differences in achievement levels, with an increase of 29.5%. A qualitative analysis allowed to collect events and comments from teachers, who stated that the SG constitutes a potential tool to develop learning strategies